Dampak Pembelajaran Gilir Ganda di Sekolah Menengah Umum - H. Sriyanto (Universitas Negeri Malang, 2016)
The main purpose of this research was to know the impact of double shift learning at Senior High School (SMU). The sample consisted of 8 SMUs in East Kalimantan selected purposively. Data were collected from students and teachers by a questionnaire, documentary study and interviews, and analyzed in percentage measures. The result showed that the teachers' productivity was low. The students' capability on morning shift was better than those on afternoon shift. The teachers and the students tended to resist the double shift system in their SMUs. There were many obstacles in school administration. The number of students in state SMUs was more than in private SMUs